The livestock insurance as a protection mechanism for livestock against catastrophic climatic events - Santiago-Hernández, Nancy; Altamirano-Cárdenas, J. Reyes; Santoyo-Cortés, Vinicio Horacio; Salas-González, José María (Ecosistemas y Recursos Agropecuarios, 2022)
To identify success factors and weaknesses in coverage in the main insurance variables and regional distribution in México, data on protected animal units, the amount of premiums contributed by producers, the federal and state governments and the sum insured were used. With resources paid in 83% from subsidies and 17% from farmers, and with the participation of five insurance institutions and an insurance fund, up to 83 million animal units were protected, covering all producers in the National Livestock Register. With cluster analysis, three groups of states were obtained and with the analysis of variance, significant statistical differences were found (p < 0.05) in the amount of premiums paid, average protected value and number of emergency and disaster declarations. The flexibility of the program to incorporate insurance schemes and the subsidy of the premium with public resources were identified as success factors.